Genetic Susceptibility and Sleep Disturbance in Black Mothers of Preterm Infants: An Exploratory Study - Shih-Yu Lee; Hui-Chin Hsu (SAGE Publishing, 2016)
Serotonin (5HT) is involved in emotion and sleep regulation and the 5HT transporter (5HTT) regulates 5HT function. A common 44-base pair deletion (short allele) or insertion (long allele) polymorphism in the promoter region of 5HTT (5-HTTLPR) is differentially associated with 5HTT transcription efficiency. Under stressful conditions, the short allele of 5-HTTLPR has been associated with depression and sleep disturbance. Black women are at higher risk for preterm labor and depressive symptoms. Thus, this exploratory study aimed to examine whether depressive symptoms and sleep disturbance in Black mothers would vary as a function of the 5-HTTLPR genotype when they faced the stress of infant hospitalization after preterm birth at early postpartum. A total of 30 Black mothers filled out a battery of questionnaires, including the Perceived Stress Scale, Edinburgh Postnatal Depression Scale, and General Sleep Disturbance Scale. A wrist actigraph was used to assess total sleep time and circadian activity rhythms. Buccal cells from saliva were collected to test the 5-HTTLPR genotype. Results showed that about 38% of the mothers were heterozygous for the short (S/L) allele, and 62% were homozygous for the long (L/L) allele. Mothers' perceived global stress, depressive symptoms, and circadian activity rhythms did not vary with their 5-HTTLPR genotypes. Unexpectedly, mothers with the L/L allele reported greater sleep disturbances than those with the S/L allele. Ethnic specificity in genetic susceptibility to stress was discussed.